2005
DOI: 10.1002/bdra.20152
|View full text |Cite
|
Sign up to set email alerts
|

Novel karyotypic changes detected by comparative genomic hybridization in a case of congenital cervical immature teratoma

Abstract: None of the identified chromosomal aberrations have been previously associated with congenital extragonadal teratomas. Important genes that lie in these DNA regions may be implicated in the pathogenesis of congenital teratomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…In particular, Gli2 and Gli3 are regulated much like Ci, becoming repressors or activators, depending on levels of Hh. The Rdx ortholog SPOP lies in 17q21.33, a chromosomal region that has been linked with ovarian cancer and cervical immature teratoma (Bernardini et al, 2005;Miliaras et al, 2005). Future studies will determine whether the Rdx orthologs SPOP or LOC339745 modulate Gli levels and Hh-mediated responses, and even contribute to cancer.…”
Section: Developmentmentioning
confidence: 99%
“…In particular, Gli2 and Gli3 are regulated much like Ci, becoming repressors or activators, depending on levels of Hh. The Rdx ortholog SPOP lies in 17q21.33, a chromosomal region that has been linked with ovarian cancer and cervical immature teratoma (Bernardini et al, 2005;Miliaras et al, 2005). Future studies will determine whether the Rdx orthologs SPOP or LOC339745 modulate Gli levels and Hh-mediated responses, and even contribute to cancer.…”
Section: Developmentmentioning
confidence: 99%
“…Speculations regarding probable genetic changes on comparative genomic hybridizations are being sought and they include 1p21.1 amplification, 9p22 deletion, and 17q21.33 1-copy gain. [3] Associated malformations include imperforate anus, Chondrodystrophia fetalis, hypoplastic left ventricle with pulmonary hypoplasia, cystic fibrosis, absence of corpus callosum, and arachanoid cyst, though very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Teratomas are usually benign neoplasms with an incidence of about 1 in 40,000 births. 1,2 When mature and cystic, they have a smorgasbord of features that include hair, fat, bone, and brain tissue to name just a few. Remarkably, one study reported a retroperitoneal teratoma containing two fetuses in a 5-day-old girl.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Malignant teratomas are generally solid neoplasms that have a high mortality if left untreated. 2,5 These neoplasms are classified as germinal, non-germinal, or immature metastatic. 4 Their origin is not completely understood; however it is suggested that they do not arise simply from a metaplastic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation